Samsonite: Case Study - Naveed Muhammad Khan; Tauseef A Qureshi (Institute of Business Management, 2017)
This case study aimed at shedding light on the new emerging trends of business observed in the Asian region. Today, big multinationals are learning from Asia and applying best practices, developed in this continent, in their operations worldwide spanning from USA, South America and Europe. In particular, this case study paid focus on the strategy adopted by Timothy Charles Parker, the Chairman of the Board of Directors, Samsonite International S.A, incorporated in March 2011. It also focused on the turnaround strategy applied by him for the Samsonite (Luggage Company). Charles Parker is a man with a reputation for turning around companies from losses to prof itability. He was put in charge by the Board to revive Samsonite that was continuously losing its strength and market share in the year of 2009. From this perspective, this study tried to explore the methodology adopted by Timothy Charles Parker to successfully revive the company. It is also noteworthy to note how Timothy Charles Parker paid careful attention to the integration strategy by Ramesh Tainwala in India to support the Samsonite operations in American and European operations. Furthermore, Asian region was also used for tapping funds from the stock market because of damage to the brand equity of Samsonite in the developed markets. Within the period of merely seven years, Samsonite is now one of the most thriving and successful luggage companies in the world and its share is most sought after in Hong Kong stock market. Based on the studies case, it can be recommended that management practices developed in Asian region can also be adopted in order to revive.